MicroRNA: Another Pharmacological Avenue for Colorectal Cancer? - Wu, Xueliang; Yan, Fuguo; Wang, Likun; Sun, Guangyuan; Liu, Jinyu; Qu, Ming; Wang, Yicheng; Li, Tian (Frontiers in Cell and Developmental Biology, 2020)
MicroRNAs (miR) are single-stranded RNA of 21-23 nucleotides in length that repress mRNA translation and induces mRNA degradation. miR acts as an endogenous factor of gene expression and plays a crucial part in cancer biology such as cell development, proliferation, differentiation, and apoptosis. Numerous research has indicated that dysregulation of miR associates with colorectal carcinogenesis. In this review article, we firstly introduce the background of miR and colorectal cancer, and the mechanisms of miR in colorectal cancer, such as the proliferation, apoptosis, and progression. Then, we summarize the theranostic value of miR in colorectal cancer. Eventually, we discuss the potential directions and perspectives of miR. This article serves as a guide for further studies and implicate miR as a potent theranostic target for colorectal cancer.